Healthcare in Crisis: Accessibility Challenges for Flood-Affected Rural Communities in Sunamganj District of Bangladesh - Sojib Bin Zaman; Ariful Haque; A.S.M. Rabbane; Ishtiaq Mohiuddin; Zahida Fizza Kabir; Pronoy Saha; Sumaiya Khan Sezuti; Sadia Shabnam; Choudhury Md. Fahim Ragib; Tajwar Hoque; Asadur Rahman; Mohammad Sakhawat Hosen; Raihan Khan (Public Health of Indonesia, 2026)
Background: Climate change has intensified the frequency and impact of flash floods, endangering millions of lives through livelihood disruption, property damage, and a surge in waterborne diseases. In response to the devastating flash floods in Sunamganj district of Bangladesh, the Sajida Foundation, a nonprofit organization, implemented a post-flood rehabilitation program to address healthcare needs. Objective: This study aims to explore the challenges and lessons learned from the healthcare response provided during the rehabilitation program in Sunamganj. Methods: The study utilized a mixed-methods approach, including qualitative interviews and quantitative analysis of patient data collected from health camps conducted during the rehabilitation effort. Descriptive statistics were employed to analyze healthcare service utilization, satisfaction, and disease patterns among the affected population. Results: The analysis revealed that 71% of patients seeking treatment were female, with the most prevalent diseases being diarrhea (32%), fever, cold, and cough (27%), generalized weakness (21%), hypertension (11%), and skin diseases (9%). Fever, cold, and cough were particularly common among children (7%), while the most vulnerable age group was 20–60 years (53%). Key challenges identified included shortages of healthcare services, medical supplies, and healthcare providers. Strengthening healthcare systems, ensuring adequate medical supplies, and fostering community resilience are critical to improving healthcare outcomes in flood-affected areas. Conclusion: The study highlights significant gaps in healthcare accessibility during post-flood rehabilitation efforts. It emphasizes the need for a multi-sectoral and data-driven approach to emergency healthcare response and long-term rehabilitation. Lessons from this study can inform policy and programmatic strategies for future emergency response initiatives.